The versatility of macrophage heterogeneity in liver fibrosis - Gao, Chun-Chen; Bai, Jian; Han, Hua; Qin, Hong-Yan (Frontiers in Immunology, 2022)
Liver fibrosis is a highly conserved wound healing response to liver injury, characterized by excessive deposition of extracellular matrix (ECM) in the liver which might lead to loss of normal functions. In most cases, many types of insult could damage hepatic parenchymal cells like hepatocytes and/or cholangiocytes, and persistent injury might lead to initiation of fibrosis. This process is accompanied by amplified inflammatory responses, with immune cells especially macrophages recruited to the site of injury and activated, in order to orchestrate the process of wound healing and tissue repair. In the liver, both resident macrophages and recruited macrophages could activate interstitial cells which are responsible for ECM synthesis by producing a variety of cytokines and chemokines, modulate local microenvironment, and participate in the regulation of fibrosis. In this review, we will focus on the main pathological characteristics of liver fibrosis, as well as the heterogeneity on origin, polarization and functions of hepatic macrophages in the setting of liver fibrosis and their underlying mechanisms, which opens new perspectives for the treatment of liver fibrosis.